2020
DOI: 10.1016/j.ijantimicag.2020.106053
|View full text |Cite
|
Sign up to set email alerts
|

Macrolides and viral infections: focus on azithromycin in COVID-19 pathology

Abstract: The emergence of the new COVID-19 virus is proving to be a challenge in seeking effective therapies. Since the most severe clinical manifestation of COVID-19 appears to be a severe acute respiratory syndrome, azithromycin has been proposed as a potential treatment. Azithromycin is known to have immunomodulating and antiviral properties. In vitro studies have demonstrated the capacity of azithromycin in reducing production of pro-inflammatory cytokines such as IL-8, IL-6, TNF alpha, reduce oxidative stress, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 68 publications
(47 reference statements)
0
82
0
3
Order By: Relevance
“…Azithromycin is a commonly used macrolide antibiotic that has antiviral properties mainly attributed to reduced endosomal transfer of virions as well as established anti-inflammatory effects. 27 It has been commonly used in COVID-19 studies initially based on French reports demonstrating markedly reduced durations of viral shedding, fewer hospitalizations, and reduced mortality combination with HCQ as compared to those untreated. 28 , 29 In the large inpatient study (n = 2451) discussed previously, those who received azithromycin alone had an adjusted HR for mortality of 1.05, 95% CI 0.68-1.62, and P = 0.83.…”
Section: Combination Antiviral Therapymentioning
confidence: 99%
“…Azithromycin is a commonly used macrolide antibiotic that has antiviral properties mainly attributed to reduced endosomal transfer of virions as well as established anti-inflammatory effects. 27 It has been commonly used in COVID-19 studies initially based on French reports demonstrating markedly reduced durations of viral shedding, fewer hospitalizations, and reduced mortality combination with HCQ as compared to those untreated. 28 , 29 In the large inpatient study (n = 2451) discussed previously, those who received azithromycin alone had an adjusted HR for mortality of 1.05, 95% CI 0.68-1.62, and P = 0.83.…”
Section: Combination Antiviral Therapymentioning
confidence: 99%
“…111 Interestingly, the MoA of azithromycin and HCQ may be related to the modulation of the endosomal and trans-Golgi network pH. 112,113 In addition, azithromycin plays a role in regulating interleukin production that might help to control the immune response and prevent symptom worsening. [114][115][116] Azithromycin may also inhibit viral invasion by interfering with the CD147-mediated recognition mechanism.…”
Section: Immunomodulatorsmentioning
confidence: 99%
“…Azithromycin is an antibiotic that has also antiviral activity in respiratory viral infections 111 . Interestingly, the MoA of azithromycin and HCQ may be related to the modulation of the endosomal and trans‐Golgi network pH 112,113 . In addition, azithromycin plays a role in regulating interleukin production that might help to control the immune response and prevent symptom worsening 114‐116 .…”
Section: Drug Repositioning Strategies For Covid‐19 Treatmentmentioning
confidence: 99%
“…Azithromycin was detected to possess anti-inflammatory and immunomodulating actions in addition to antiviral properties because of its ability to minimize the production of pro-inflammatory cytokines particularly IL-6 and TNF-α, noxious oxidative radicals as well as to improve T-helper functions. However, the preliminary studies have demonstrated that using azithromycin should be in caution due to its potential arrhythmogenic threat, especially in highly risk COVID-19 patients (Pani et al, 2020).…”
Section: Current Therapiesmentioning
confidence: 99%